Multiple Idiopathic Cervical Root Resorption: A Challenge for a Transdisciplinary Medical-Dental Team - Emily Y. Chu; Janina Golob Deeb; Brian L. Foster; Evlambia Hajishengallis; Martha J. Somerman; Vivek Thumbigere-Math; Vivek Thumbigere-Math (Frontiers Media S.A., 2021)
The goal of this perspective article is to use multiple idiopathic cervical root resorption (MICRR) as a model to demonstrate the need for transdisciplinary collaborations, from basic science to treatment planning, to improve the quality of health care for all. This is not a review of the literature on the current state of MICRR. Tooth root resorption is a normal physiological process required for resorption and exfoliation of primary teeth; however, root resorption of adult teeth is largely pathological. MICRR is an aggressive form of external root resorption, which occurs near the cemento-enamel junction (CEJ). The cause of MICRR remains elusive, however, it is mediated primarily by osteoclasts/odontoclasts. Accumulating case studies and experiments in animal models have provided insights into defining the etiologies and pathophysiological mechanisms for MICRR, which include: systemic conditions and syndromes, inherited genetic variants affecting osteoclast/odontoclast activity, altered periodontal structures, drug-induced root resorption and rebound effects after cessation of anti-resorptive treatment, chemotherapy, exposure to pets or viral infections, and other factors such as inflammatory conditions or trauma. To determine the causative factors for MICRR, as well as other oral-dental conditions, at minimum, a comprehensive health history should be collected for all patients by dental care providers, discussed with other health care providers and appropriate collaborations established. The examples highlighted in this perspective emphasize the need for transdisciplinary research collaborations coupled with integrated management strategies between medicine and dentistry in order to identify cause(s) early and improve clinical outcomes.